Adubação de sistemas: estratégias sustentáveis para utilização de nitrogênio e potássio em sistema de integração lavoura - pecuária - Tatto, Wilson Henrique (2021)
The success of agricultural production in integrated crop-livestock systems is based on the appropriate use of management strategies adopted in the pasture phase. In southern Brazil, many studies have confirmed the residual effect of fertilizing cool season pastures for grain crops grown in sequence, including the possibility of omitting during cash-crop season. In this context, based on the theoretical literature of the system-level fertilization the objective of this work is to determine the best strategy of recommendation of nitrogen and potassium fertilization that allows to obtain high forages and grains productivity in integrated crop-livestock system. The experimental data used in the analyzes came a long-duration experiment of integrated crop-livestock system located in the town of Abelardo Luz – SC. The agricultural season’s used were: Summer 2013/14 (corn); winter 2017 (black oat pasture) and summer 2017/18 (corn). During the experimental period, was analyzed of the nutritional status of nutrients N, P and K of the pasture and crops, the grains yield of corn in kg ha-1 and the cause and effect relation-ship of nitrogen fertilization realized in the pasture phase over the components of maize production in succession. The experimental design in corn phase was a randomized complete block using a split-split plot with three replications. On each of the 12 experimental plots (two pasture N-K fertilization rates × six replications), four N-K corn fertilization rates (0 – 0, 100 – 50, 200 – 100 and 300 – 150 kg of N- K2O ha-1 applied in same moment). It was found carryover effect of N from the cool-season pasture grazed and fertilized with N-K provided adequate N during all stages of a subsequent corn crop. The P nutrition in corn was excellent at all stages of maize development independently of fertilization or not in the previous pasture. Precision diagnosis of the nutritional status of N during the early stages of pasture and corn development can provide support for better N fertilization recommendations, showing that the use of dilution curves can be an innovative way of managing N. The relationship between the yield components and the grain yield in maize grown in a crop-livestock system are dependent on the fertilization system used. With the results found in this work, it is concluded that the nitrogen and potassium fertilization in broadcast during the pasture phase is able to increase the forage production and sustain the yield of corn in the successor in integrated crop-livestock system.